Institutional environment and credibility of public promotion of renewable energy. Lesson's from India's grid solar energy management in Gujarat state - Phungmayo Horam; Kai Rommel; Dipak Joshi (ISM Research Journal, 2014)
Located in the equatorial Sunbelt of the Earth, emerging economies such as India have huge potential for the development of solar energy. India's concerted public promotion of the sector through the National Solar Mission has enabled the growth of over 1 GW grid solar power over the past three years. However, the sectorial growth at the state level has shown a significantly different outcome, with states such as Gujarat contributing more than half of the nation's installed capacity. Many other states contribute less than 1 %. Such lopsided growth at the regional level shows serious concerns for the sustained growth of the sector and for meeting India's overall national target of 20 GW by 2022. Experience around the world has shown the critical importance of local institutional environment in successfully impeding or stimulating public promotion of renewable energy. Literature on India's solar energy development however has so far been largely concentrated at the national level, sidelining the institutional dynamics affecting the sectorial growth at the regional level. This paper seeks to address this gap using the institutional analysis of factors affecting the successful public promotion of grid solar energy at the state level, by studying the case of Gujarat through stakeholder and expert interview. Following the new institutional economic perspective, this study develops a transaction cost economics cum positive political theory approach with focus on the role of intuitions in restraining actor's opportunistic behaviour and its implications on the credibility of governance structure.
Keywords: 650